Correction: Zhang et al. Expression Profiling and Functional Analysis of Candidate Odorant Receptors in Galeruca daurica. Insects 2022, 13, 563 - Jing-Hang Zhang; Ling Li; Na Li; Yan-Yan Li; Bao-Ping Pang (Insects, 2025)
In the original publication [...]